ISOLASI DAN IDENTIFIKASI SENYAWA FLAVANOID PADA DAUN ADAM HAWA (Rhoe discolor) - Sitorus, Risma Meidy Hardina; Wullur, Adeanne; Yamlean, Paulina (UNIVERSITAS SAM RATULANGI, 2012)
One of the plants can be used as a drug crop is Adam Hawa (Rhoe discolor) are thought to containflavanoid compounds, it is seen from the purple on the leaf. This study aims to determine the presenceor absence of flavonoids and other types of flavanoid compounds are contained in the leaf AdamHawa (Rhoe discolor). Isolation of flavonoids is done by maceration. Flavanoid compoundidentification is done by preparative Thin Layer Chromatography (KLTP) using the eluent n-butanol:acetic acid: water (BAA) with a ratio of 4:1:5. Identification of flavanoid compounds made with UVVisspectrophotometer. The results showed the leaf extract of Adam Hawa (Rhoe discolor) containsflavanoid compounds. Seen from the results of preparative thin layer chromatography to yield threespots with Rf value of 0.09; 0.36, and 0.71. Based on the analysis of UV-Vis spectrophotometer, threeisolates with Rf value of 0.71 has a maximum wavelength of 275 nm.Keyword : Adam Eve leaf (Rhoe discolor), Flavanoid, Preparative Thin Layer Chromatography(KLTP), UV-Vis spectrophotometer.